Developing an Urang Banjar Personality Inventory - Putra, Ansyari Adytia; Sugiharto, DYP; Sutoyo, Anwar (Universitas Negeri Semarang, 2022)
In guidance and counseling services, instruments are heavily needed as a means of data collection and consideration prior to providing both preventive and curative services. However, the existing instruments in Indonesia are a way too general due to Indonesia various ethnicity and races. Thus, the present study attempted to produce a valid and reliable personality inventory for guidance and counseling teachers to measure senior high school students personality. It involved 175 students selected purposively from 4 public schools in Banjarmasin City in South Kalimantan with the age range of 15-19 years. Its validity was analyzed using a Pearson’s product moment test, while the reliability was measured using an alpha technique. Of these tests, there obtained the final inventory with the total of 44 items with 22 favorable items and 22 unfavorable items. It also got the range between 0.375 up to 0.726 with the alpha coefficient of 0.846 up to 0.899. Thus, this Banjar culture-based personality inventory can be implemented for the guidance and counseling services at school.